.A Book Review of Music in Turkey: Experiencing Music, Expressing Culture - Hadi Sepehri; Houman Asadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2020)
.The book “Music in Turkey: Experiencing Music, Expressing Culture”, published in 2018, contains general information on the current life and culture of Turkish music with a focus on Istanbul. This book provides details on musical geography, music history, instruments, theoretical concepts of music, and twentieth-century musical developments, along with a chapter on the music recording and publishing industry. The author of the book in question has been able to express some of the most current topics in Turkish music culture in the book; he has covered almost all existing styles and related executive, educational, and publishing areas. As a result, the book is comprehensive, semi-specialized, and useful for anyone interested in the subject, especially for ethnomusicology students, providing an overview of contemporary Turkish music culture. After reading the book, problems with translation, including issues related to the correct pronunciation of Turkish idioms, correct spelling, and nouns in Persian, as well as the technical and musical issues, were noted in the text in detail.